Accounting for business combinations : - Burton, John C. (Financial Executives Research Foundation, 1970)
Covers a broad range of transactions and draws on a variety of accounting literature to amplify the text in FASB Accounting Standards CodificationTM Topic 805, Business Combinations, and Topic 350, Intangibles Goodwill and Other, for U.S. standards, and International Financial Reporting Standards 3, Business Combinations, and International Accounting Standard 38, Intangible Assets, for international standards, as issued by the International Accounting Standards Board.